2019
DOI: 10.4236/tel.2019.93033
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion and Economic Growth in WAEMU: A Multiscale Heterogeneity Panel Causality Approach

Abstract: This paper examines the causal relationship between Financial Inclusion and economic growth in the West African Economic and Monetary Union (WAEMU) from 2006 to 2015. We combined the heterogeneity panel causality test proposed by [1] with the Maximal Overlap Discrete Wavelet Transform (MODWT) to analyze the bi-directional causality at different time scales. We used two Financial Inclusion indicators: the overall rate of demographic penetration of financial services (Financial Inclusion supply) and the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
5
13
0
Order By: Relevance
“…The results also explain that LogGDPC i,t causes LogFP1 i,t , LogFP2 i,t , LogFP3 i,t , and LogFP4 i,t at 1%. Thus, we find that there exists reverse causality between financial permeation and economic growth consistent with the findings of Evans and Lawanson (2017), Gourène and Mendy (2017), and Sharma (2016). (Breusch & Pagan, 1980) 118.357 .000 CD LM1 (Pesaran, 2004) 11.638 .013 CD LM2 (Pesaran, 2004) -2.013 .000…”
Section: Granger Non-causality Testsupporting
confidence: 90%
“…The results also explain that LogGDPC i,t causes LogFP1 i,t , LogFP2 i,t , LogFP3 i,t , and LogFP4 i,t at 1%. Thus, we find that there exists reverse causality between financial permeation and economic growth consistent with the findings of Evans and Lawanson (2017), Gourène and Mendy (2017), and Sharma (2016). (Breusch & Pagan, 1980) 118.357 .000 CD LM1 (Pesaran, 2004) 11.638 .013 CD LM2 (Pesaran, 2004) -2.013 .000…”
Section: Granger Non-causality Testsupporting
confidence: 90%
“…Also, the periodicity of the relationship under review was not sufficiently long. A mutual causality concerning the two factors has also been noted by others [11,74]. Interestingly, panel data analysis was applied in Kim, Yu and Hassan [11], which described the complementary effect of inclusive financing on the growth of the economy in the sovereignties of the Organization of Islamic Cooperation (OIC).…”
Section: Empirical Frameworkmentioning
confidence: 72%
“…The study by Ibrahim and Alagidede [82] in SSA however shows that, while financial development positively and significantly influences economic growth, below a certain estimated threshold, finance is largely insensitive to growth while significantly influencing economic activity for countries above the thresholds. Others argue that inclusive financing and the growth of economies simply have independence or an inconsequential influence [74].…”
Section: Empirical Frameworkmentioning
confidence: 99%
“…Others have concluded that economic growth drives financial inclusion; the demand-following hypothesis (Babajide et al, 2015;Evans, 2015). Others have observed a reciprocal causality between the two variables (Gourène andMendy, 2017 andKim et al, 2018). Others argue that there is simply independence or unimportant influence between financial inclusion and the growth of economies (Gourène and Mendy, 2017).…”
Section: Financial Inclusion and Economic Growthmentioning
confidence: 99%
“…A higher Z-score therefore designates a more stable banking system. Based on the works of Gourène and Mendy (2017) who used GDP per capita growth as an indicator of economic growth, the study proxy economic growth with GDP per capita growth to allow for cross country comparisons and capturing of income distribution effects. The values are obtained from the World Bank Development Indicators Database.…”
Section: Data Sources and Variable Descriptionmentioning
confidence: 99%